2019
DOI: 10.1103/physrevlett.122.067401
|View full text |Cite
|
Sign up to set email alerts
|

Bright Luminescence from Indirect and Strongly Bound Excitons in h-BN

Abstract: A quantitative analysis of the excitonic luminescence efficiency in hexagonal boron nitride (hBN) is carried out by cathodoluminescence in the ultraviolet range and compared with zinc oxide and diamond single crystals. A high quantum yield value of ∼50% is found for hBN at 10 K comparable to that of direct bandgap semiconductors. This bright luminescence at 215 nm remains stable up to room temperature, evidencing the strongly bound character of excitons in bulk hBN. Ab initio calculations of the exciton disper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(106 citation statements)
references
References 54 publications
2
103
1
Order By: Relevance
“…By comparing these two dispersion curves, it is found that excitonic effects tend to flatten the dispersion of the noninteracting electron–hole pair due to the change of exciton effective mass as a function of q . [ 26 ] As a result, the binding energy of the lowest‐energy indirect exciton Ebi (0.16 eV) is different from that of the lowest‐energy direct exciton Ebd (0.29 eV) shown in Figure 4d. In traditional indirect‐gap semiconductors [ 7a,8b,27 ] and 2D transition metal dichalcogenides, [ 10a–c,28 ] the EHL critical temperature T c has been predicted to be a fraction of the the lowest indirect exciton binding energy (kBTc0.1Ebi, kB is the Boltzmann constant).…”
Section: Resultsmentioning
confidence: 92%
“…By comparing these two dispersion curves, it is found that excitonic effects tend to flatten the dispersion of the noninteracting electron–hole pair due to the change of exciton effective mass as a function of q . [ 26 ] As a result, the binding energy of the lowest‐energy indirect exciton Ebi (0.16 eV) is different from that of the lowest‐energy direct exciton Ebd (0.29 eV) shown in Figure 4d. In traditional indirect‐gap semiconductors [ 7a,8b,27 ] and 2D transition metal dichalcogenides, [ 10a–c,28 ] the EHL critical temperature T c has been predicted to be a fraction of the the lowest indirect exciton binding energy (kBTc0.1Ebi, kB is the Boltzmann constant).…”
Section: Resultsmentioning
confidence: 92%
“…The wavelength of the excitation-light source must be shorter than that corresponding to the band-gap energy of h-BN, that is, about 6 eV (206 nm), to excite the exciton PL band. 17,18 The optimal excitation wavelength must be sufficiently different from the wavelength of exciton luminescence at 215 nm to separate the PL component from the excitation by a far-UV interference filter. Designing the filter for a suitable transmission characteristic in this wavelength range is extremely difficult because the combinations of optical materials in the far-UV region (wavelength <230 nm) are limited.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, hBN has been demonstrated as a promising material for ultraviolet light emission [8,9]. Despite the indirect character of its bandgap, hBN exhibits highly efficient radiative recombination through phononmediated transitions due to strong electron-phonon interactions [6,7,[10][11][12][13]. It has also recently been shown to host point defects that function as bright, room temperature single photon sources, which can enable technologies such as quantum cryptography and precision sensing [14,15].…”
Section: Introductionmentioning
confidence: 99%